The effect of moderate weight loss, with or without (1, 3)(1, 6)-β-glucan addition, on subcutaneous adipose tissue inflammatory gene expression in young subjects with uncomplicated obesity - Strączkowski, Marek; Nikołajuk, Agnieszka; Majewski, Radosław; Filarski, Remigiusz; Stefanowicz, Magdalena; Matulewicz, Natalia; Karczewska-Kupczewska, Monika (Endocrine, 2018)
Purpose Obesity is characterized by insulin resistance and low-grade systemic and adipose tissue (AT) inflammation. It remains unclear whether beneficial effects of weight loss are related to AT inflammation. We aimed to assess the effect of weight loss during low-calorie diet on insulin sensitivity, AT expression of genes associated with inflammation in young subjects with obesity. Furthermore, we estimated the effects of immunomodulatory (1, 3)(1, 6)-β-glucan (BG) on the above parameters. Methods The study group comprised 52 subjects with obesity. Twelve-week dietary intervention was applied, with randomization to receive or not 500 mg BG daily. Euglycemic hyperinsulinemic clamp, subcutaneous AT biopsy were performed before and after the program. Twenty normal-weight subjects, examined at baseline, served as a control group. Results At baseline, obese subjects had lower insulin sensitivity, lower AT ADIPOQ , JAK1 , and JAK2 expression and higher AT expression of LEP , IL6ST , STAT3 , MIF , CCL2 , MMP9 , and IL18 . Forty obese subjects completed dietary intervention program, which resulted in 11.3% weight loss and 27% increase in insulin sensitivity (both p < 0.0001). AT IL6R , IL6ST , JAK1 , and JAK2 expression increased, whereas MIF , CCL2 , MMP9 , and IL18 gene expression did not change in response to weight loss. BG addition had no effect on any of the parameters studied. Conclusions Our data indicate that reduction in AT inflammation is not required for an improvement in insulin action during weight loss in subjects with uncomplicated obesity. BG does not have effects during dietary intervention.